Free Recall Enhances Subsequent Learning - Arnold, Kathleen M. (2013)
Testing, or retrieval practice, has become a central topic in memory research. One potentially important effect of retrieval practice has received little attention, however: Retrieval practice may enhance, or potentiate, subsequent learning. We introduce a paradigm that can measure the indirect, potentiating effect of free recall tests on subsequent learning, and then test a hypothesis for why tests have this potentiating effect. In two experiments, the benefit of a restudy trial was enhanced when prior free recall tests had been taken. Results from a third correlational study suggest that this effect may be mediated by the effect of testing on organization. Not only do encoding conditions impact later retrievability, but also retrieval attempts impact subsequent encoding effectiveness.